Improving the Prediction of Risk for Anxiety Development in Temperamentally Fearful Children - Buss, Kristin A. (Curr Dir Psychol Sci, 2016)
Pediatric anxiety disorders are among the most common disorders in children and adolescence resulting in both short-term and long-term negative consequences across a variety of domains including social and academic. Early fearful temperament has emerged as a strong predictor of anxiety development in childhood; however, not all fearful children become anxious. The current article summarizes theory and evidence for heterogeneity in the identification of temperamentally fearful children and trajectories of risk for anxiety. The findings presented in this article reveal that identification of subgroups of fearful temperament improves prediction of who is at risk for developing anxiety problems.